PELATIHAN PERENCANAAN KEUANGAN USAHA YANG TEPAT BAGI PELAKU UMKM DAN KELOMPOK PKK DI DESA GANDASOLI - Dendi Purnama; Teti Rahmawati; Neni Nurhayati (Jurnal Abdimas Bina Bangsa, 2022)
MSME actors in Gandasoli Village still combine business money and personal money so it is difficult to know the benefits achieved and losses experienced and have not fully identified the costs so that they cannot reduce their business expenses. The purpose of this service is to provide knowledge and skills about business financial planning and compile the right business budget for MSME actors and PKK mothers. The participants who attended this activity were 26 people consisting of MSME actors and PKK mothers in Gandasoli Village. This activity was carried out on December 12, 2022. The methods used in the implementation of service are training using technical information presentations and simulation methods as well as assistance with individual and classical approaches. The results of this activity can increase knowledge and skills in planning business finances and compiling the right business budget. This is evidenced by their ability to practice budgeting, identifying costs and separating personal money and business money and projecting profit and loss simply